Effect of prefreezing on surface color and structural and textural properties of kiwifruit after microwave-vacuum drying with temperature control by microwave power manipulation - Ando, Yasumasa; Okada, Takeyuki (Food Science and Technology Research, 2023)
The present study describes the effects of prefreezing on drying rate, surface color, internal structure, and textural properties of kiwifruit treated with microwave-vacuum drying (MVD) under controlled-temperature conditions at 20, 30, and 40 °C. The prefreezing was effective in reducing the drying time in the MVD process under properly controlled temperature conditions. The MVD samples without prefreezing had the same level of low a* value (high greenness) as the freeze-dried sample, but the prefrozen-MVD samples showed a slight browning due to discoloration during thawing in an atmospheric pressure environment. The prefreezing suppressed sample shrinkage during the MVD process and allowed the formation of a porous structure with many large voids with thin walls. Thanks to this structure, the prefrozen-MVD samples showed textural characteristics similar to the freeze-dried sample, but the porous structure was not formed in the MVD at 20 °C, indicating that a high microwave power is required to generate a high enough vapor pressure to form the porous structure.